(untitled) (Journal of the College of Basic Education, 2022)
Values ​​are still and will remain one of the most important concepts dealt with in various humanities and social sciences. Equally, values ​​are related to human existence and determine the meaning of his actual existence, not the formal one. Individuals and even societies have no significant impact, because they did not care about values, and the world is living today in a dangerous phase. And decisive in its history, as this stage is witnessing growth that exceeds all perceptions in the field of technology and information. Communications are also witnessing a deterioration that exceeds all perceptions in the field of values ​​(i.e. the dissolution of values). The matter requires pausing for a while and contemplating what happened and what will happen if the matter continues as it is.